PREFACE - Gqaleni, Nceba; Shongwe, Vusi; Seleti, Yonah (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Preface With an estimated 5.6 million people living with HIV in 2009, South Africa’s epidemic remains the largest in the world (UNAIDS, 2010). It is approximated that 40million South Africans depend on traditional medicine for their primary health care needs and regularly visit Traditional Health Practitioners (THPs). Patients often move freely between traditional and allopathic systems of medicine. In fact, up to 90% of people living with HIV and AIDS first consult THPs before visiting practitioners of allopathic medicine. Thus THPs bear the brunt of the HIV and AIDS epidemic. With this in mind it became necessary to convene a conference where the potential contribution of traditional medicine in the fight against HIV and AIDS could be objectively assessed. It also facilitated learning and sharing experienses from practitioners, researchers, governments and NGOs/or funders that have advanced in integrating traditional medicine in HIV and AIDS. The conference covered four key priority areas in accordance with the National Strategic Plan for HIV and AIDS and STI: prevention; treatment, care and support; research, monitoring and surveillance; and financing. The Conference was titled “Traditional medicine in the era and HIV/AIDS in South Africa” and held at the International Convention Centre, Durban between 28th to 30th July 2010. This historic conference, funded by PEPFAR/CDC South Africa, was attended by more than 1500 delegates from South Africa, Belgium, Botswana, Cameroon, China, Lesotho, Nigeria, Tanzania, Uganda, United States of America, and Zambia. On each day there were 200 high school learners and 200 community members in attendance. In addition there were researchers, CAM practitioners, donors, doctors, nurses, THPs, policy makers, and members of the media. It was organised in partnership with the Department of Science and Technology, the KwaZulu-Natal Provincial Government and the University of KwaZulu-Natal and had the support of the Department of Health, the South African National AIDS Council (SANAC) and the South African Broadcasting Corporation (SABC) among others. National Parliament was represented by members of the Health and, Science and Technology Portfolio Committees, respectively. National government departments in attendance included Health, Science and Technology, and Trade and Industry. All provinces of South Africa were represented with the exception of Northern and Western Cape provinces. The House of Traditional Leaders and Local Government were represented by Her Majesty, Queen of LinduZulu, local chiefs, Mayors and Councilors. The US Government (PEPFAR) was represented by the Health Attaché in the US Embassy, US Consul General in Durban, PEPFAR Liaison Officer (KZN) and CDC (South Africa). A call for abstracts was published in 3 major national newspapers and on the internet on a number of websites. Abstract themes had to fit within the strategic areas of the National Strategic Plan for HIV/AIDS/TB. The conference received more than 70 abstracts, reviewed by a panel of national and international experts. About 50 abstracts were accepted for oral presentation and 12 as posters. Additional speakers from the 7 provincial departments of health and 7 Provincial AIDS Council THP sector representatives informed the conference on their programmes. The Department of Science and Technology and the Technology Innovation Agency shared their plans and strategies for research and development of traditional medicines in South Africa. The conference was primarily abstract-driven. Abstract contents were either research-based data using established scientific methods or demonstrated experience and information from individuals or institutions working in the field in the form of case studies or case presentations. The non-abstract-driven components of the conference addressed a variety of current viewpoints and issues including government programmes, interactive case-based sessions, and satellite symposia. The television and print media broadcasted the proceedings of the conference. Selected speakers and delegates were interviewed live. Highlights The highlights of the conference included the following: 1. South Africa could demonstrate its capacity to carry out world class clinical trials on traditional medicine. 2. Provincial Governments and Provincial AIDS Councils shared their plans and strategies to include traditional medicine in their implementations plans. 3. Traditional Health Practitioners were in full support of integrating HIV Counseling and Testing, Traditional or Medical Male Circumcision, and other national strategies in their practices but required support and capacitation for HIV testing. 4. It is necessary to intensify research on traditional medicines since a number of HIV positive patients who do not qualify for antiretroviral therapy choose them. 5. There were best practice projects promoting collaboration between traditional health practitioners and public health care workers in the fight against HIV/AIDS. 6. The media will continue to report positive and negative aspects of traditional medicine 7. The Department of Science and Technology funds the most research on indigenous knowledge systems including traditional medicines in South Africa. 8. The USA remains the largest foreign funder of HIV research and programmes on traditional medicine. This special edition carries some of the scientific papers presented at the conference. Professor Nceba Gqaleni, Chair of the Traditional Medicine in the Era of HIV and AIDS Conference Dr Vusi Shongwe, Director: Heritage, Office of the Premier, KwaZulu-Natal Government and Professor Yonah Seleti, Chief Director: National Indigenous Knowledge Systems Office, Department of Science and Technology Co-Chairpersons of the Traditional Medicine in the Era of HIV and AIDS Conference.